INVESTIGATING NONVERBAL COMMUNICATION IN ENGLISH PRESENTATIONS AT EFL CLASSROOMS - Leli Sopyanti; Muh Tahir; Fatimah Hidayahni Amin (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research explores the role of nonverbal communication (NVC) in English presentations conducted by undergraduate students in EFL (English as a Foreign Language) classrooms at Universitas Negeri Makassar, where presentations have become integral to pedagogical practices aimed at fostering critical thinking and active learning. The study aims to identify and categorize forms of nonverbal communication exhibited by EFL learners during their presentations, specifically focusing on kinesic behaviors such as gestures, facial expressions, eye contact, and posture. Utilizing qualitative methods, including systematic observation of student presentations, the research captures authentic interactions to assess how these nonverbal cues contribute to message delivery and audience engagement. By enhancing understanding of NVC within EFL education, this study not only contributes theoretically by categorizing specific behaviors and exploring their functions but also offers practical insights into developing essential communication skills vital for students' academic success and professional readiness. The findings underscore the importance of integrating nonverbal communication training into EFL curricula, empowering students to deliver impactful presentations while fostering a deeper understanding of cross-cultural communication norms. Ultimately, this research highlights the need for holistic approaches in language education that prioritize both linguistic proficiency and expressive competence, equipping learners with the skills to effectively encode and decode nonverbal signals, thereby enhancing their overall communicative competence